Evaluation of Grain Yield and some Physiological Characteristics of Common Bean (Phaseolus vulgaris L.) under Water Deficit and Molybdenum - Vahid Fathirezaee (University of Tabriz, 2021)
Abstract Background & Objective: This study was conducted to evaluate the yield and some physiological characteristics of leaves and yield of dry bean affected by water deficit stress and foliar application of molybdenum.